2010
DOI: 10.1118/1.3523621
|View full text |Cite
|
Sign up to set email alerts
|

Robust automatic rigid registration of MRI and X‐ray using external fiducial markers for XFM‐guided interventional procedures

Abstract: Purpose: In X-ray fused with MRI, previously gathered roadmap MRI volume images are overlaid on live X-ray fluoroscopy images to help guide the clinician during an interventional procedure. The incorporation of MRI data allows for the visualization of soft tissue that is poorly visualized under X-ray. The widespread clinical use of this technique will require fully automating as many components as possible. While previous use of this method has required time-consuming manual intervention to register the two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…Here, the mean RMS error for the best eight markers reduced from 3.04 mm to 0.75 mm. Both registration and localization errors are higher than in the literature [12], where a localization error of 0.32 mm and a registration error of 1.16 mm were reported, using an image intensifier system but comparable or lower than the reference paper using a flat panel detector system. Therefore, the algorithm applied on a flat panel detector system is sufficiently accurate for ventricular septal defects and electrophysiology procedures as well.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Here, the mean RMS error for the best eight markers reduced from 3.04 mm to 0.75 mm. Both registration and localization errors are higher than in the literature [12], where a localization error of 0.32 mm and a registration error of 1.16 mm were reported, using an image intensifier system but comparable or lower than the reference paper using a flat panel detector system. Therefore, the algorithm applied on a flat panel detector system is sufficiently accurate for ventricular septal defects and electrophysiology procedures as well.…”
Section: Discussioncontrasting
confidence: 59%
“…Most of the voxels have zero intensity. For this sparse problem, the volume can be filled quickly with ray-driven backprojection [16], [12]. In ray-driven backprojection, the 2-D marker centers are iteratively projected back on the volume, implying that only non-zero voxels have to be processed.…”
Section: Reconstruction Of 3-d Marker Position In X-raymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works on on MRI/X-ray registration were applied to interventional imaging [84,85,86], angiographic imaging [87,88,89,90,91,92,93], cerebral [93,94,86,95], cardiac and cardiovascular imaging [96,97,98,99,100,101], and several other fields [102,103,104,105,106,107]. A detailed review of MRI/X-ray and other 2D/3D registration techniques can be found in [108].…”
Section: Related Workmentioning
confidence: 99%